Determinants of the Financial Performance: Evidence from Indonesian Manufacturing Companies - Permatasari Cahyaningdyah; Mukti Prasaja; Abdurrahman Maulana Yusuf (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
This study aims to investigate the determinants of the financial performance of manufacturing companies in Indonesia. Financial performance is proxied by return on assets, while the determining factors in this study include capital structure (leverage), institutional ownership, audit quality, and firm size. This study uses a quantitative method. The samples were determined through the purposive sampling method, which resulted in a sample of 112 manufacturing companies in Indonesia during the 2018-2020 period—hypothesis testing by performing multiple linear regression using STATA. The results show that leverage and audit quality significantly influence the company's financial performance. Meanwhile, institutional ownership and company size do not affect the financial performance of manufacturing companies in Indonesia.